Curation of scientific content in social media of Ibero-American Communication journals - Artigas, Wileidys (2022)
A study is presented on the use of content curation in the publications made by the scientific Ibero-American journals of Communication in their social networks. The reason for the research is to help better understand the characteristics and forms that content curation can take on by a scientific journal on its social networks. It is a descriptive investigation, which is based on the research techniques of the content analysis of the selected products, combining a quantitative approach of the presence of the items, and a qualitative approach in terms of its analysis and the extraction of data examples of good practice. The results show the degree of presence of Ibero-American Communication journals in social networks, the level of implementation of curation in their publications, their main themes and techniques and a series of examples of good practices that can serve as references for other journals. Among the conclusions are the low presence in social networks of the journals studied, the high presence of curation in their publications about the contents of the last issue published as well as various advertisements as major themes, and the prominence of Commenting and Summarizing as techniques of curation.